The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1755-5922.2008.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan versus Dobutamine in Heart Failure Patients Treated Chronically with Carvedilol

Abstract: Introduction: Although beta-blockers are highly effective in the treatment of heart failure (HF), many patients with HF receiving a beta-blocker continue to become decompensated and require hospitalization for worsening HF. Levosimendan and dobutamine are used to manage decompensated HF, but their comparative effects on left ventricular (LV) function in patients prescribed beta-blockers are unknown. Aims: The aim of this study was to compare the effects of dobutamine and levosimendan on LV systolic and diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In a study involving 40 patients with decompensated HF, Duygu H et al observed significant increases in LVEF, Sm, Dt, and Em and significant decrease in E/A ratio and systolic pulmonary artery pressure (SPAP) among subjects receiving levosimendan as compared to those receiving dobutamine. In dobutamine patients, no significant alterations were found in systolic and diastolic LV parameters as well as in SPAP 13 . In our study, lateral and septal Sm velocity showed a significant increase following both inotropic agents, with no significant between-group differences.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In a study involving 40 patients with decompensated HF, Duygu H et al observed significant increases in LVEF, Sm, Dt, and Em and significant decrease in E/A ratio and systolic pulmonary artery pressure (SPAP) among subjects receiving levosimendan as compared to those receiving dobutamine. In dobutamine patients, no significant alterations were found in systolic and diastolic LV parameters as well as in SPAP 13 . In our study, lateral and septal Sm velocity showed a significant increase following both inotropic agents, with no significant between-group differences.…”
Section: Discussionmentioning
confidence: 73%
“…This was the only significant treatment-related electrolyte alteration in our patients. Duman D et al compared the effects of dobutamine and levosimendan on SBP, DBP, and HR and found no significant differences 12, while Duygu H et al observed a significant increase in these three parameters in dobutamine patients, with no significant changes with levosimendan 13 . In our study, dobutamine treated patients had an average increase of 11 mmHg in SBP as compared to a 16.7 mmHg reduction in levosimendan treated patients, suggesting a predilection toward hypertension and hypotension for these two treatments, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In studies comparing levosimendan and dobutamine, some showed significant improvement in LVEF [15,20,21] both with levosimendan and dobutamine, but in a study in which patients were treated with carvedilol [17], the dobutamine group did not show an improvement in LVEF. In our study, LVEF significantly improved in the levosimendan group, but not in the dobutamine group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing levosimendan and dobutamine using echocardiographic parameters generally performed a second echocardiographic examination just after inotrope infusions [15][16][17]. We performed echocardiographic measurements 5 days after the initiation of infusions to determine whether the favorable effects of the levosimendan and dobutamine continue following infusions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is potential benefit of combined therapy with beta-blockers and levosimendan when compared to dobutamin (14) . Accordingly, some recent trials presented beneficial hemodynamic effects of levosimendan in comparison to dobutamine in patients with acute decompensated HF treated with beta-blockers (15)(16)(17) . We, in this study, successfully used levosimendan in decompensated HF patients treated concomitantly with beta-blocker drugs.…”
Section: Discussionmentioning
confidence: 99%